Prognostic significance of modern tools for stratification of sudden cardiac death risk (case study of highly-skilled footballers) - Zadvoryev, S. F.; Lyuik, L. V.; Krysyu, O. B.; Obrezan, A. G. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to assess the prevalence of significant electrocardiogram abnormalities and the prognostic value of the existing risk of sudden death in highly-skilled football players.